Isolation, characterization and identification of potential actinobacteria with antifungal activities towards chilli anthracnose - Lim, Jeffrey Seng Heng; Md. Shah, Umi Kalsom; Hamzah, Halizah (Academic Journals, 2011)
Actinobacteria from the genus of Streptomycetes have been regarded as the most potent producers of bioactive compounds in the world. In this study, a total of 132 isolates of actinobacteria were isolated from rhizospheres of various plant species planted at MARDI Langkawi Agro Technology Park, Malaysia. These isolates were screened for the ability to inhibit the growth of pathogenic fungi, Colletotrichum capsisi and Colletotrichum gloeosporioides isolated from chilli fruit. From these screening it revealed that 45 isolates of actinobacteria were able to produce antifungal activity towards C. capsici, while 67 isolates produced antifungal activity towards C. gloeosporioides. Out of these 132 isolates, 2 of the best antifungal-producer were selected and identified as Streptomyces spp. strain PM2 and PM4. Observation using scanning electron microscope (SEM) showed that the spore surface for both Streptomyces spp. strain PM2 and PM4 were rough and spiky. Physiological characterization of both strains showed their ability to grow in 1 to 4% of NaCl, growth temperature of 17 to 35°C and pH of 5 to 11. The ability of these Streptomyces spp. to secrete antifungal compounds may have been related to the availibility of the carbon sources. These findings suggest that Streptomyces spp. strain PM2 and PM4 are potential candidate for biocontrol against anthracnose disease.